2016
DOI: 10.1080/00071668.2015.1119245
|View full text |Cite
|
Sign up to set email alerts
|

The screening and evaluation of herbs and identification of herbal combinations with anti-viral effects on Newcastle disease virus

Abstract: A total of 25 "heat-clearing and detoxifying" herbs used in Chinese medicine were investigated for their cytopathic effects on the growth of Newcastle Disease virus (NDV) in a chicken fibroblast cell line. The 5 herbs with the highest virus inhibitory effects were Herba agastaches, Flos chrysanthemi indici, Rhizoma anemarrhenae, Astragalus root and Baikal skullcap root and these were used in herbal formulations. Anti-NDV activities of 4 formulations were tested on the growth of NDV in the DF-1 fibroblast cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…APS regulates immune functions by stimulating the release of cytokines and affecting the secretion of immunoglobulin and conduction of immune signals. The immunomodulatory effects of APS against various viruses have been demonstrated (Shi et al, 2014;Xue et al, 2015;Wang et al, 2016;Zheng et al, 2020). APS has also been investigated for its enhancement of the immunity of COVID-19 patients (Adhikari et al, 2020;Meletis and Wilkes, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APS regulates immune functions by stimulating the release of cytokines and affecting the secretion of immunoglobulin and conduction of immune signals. The immunomodulatory effects of APS against various viruses have been demonstrated (Shi et al, 2014;Xue et al, 2015;Wang et al, 2016;Zheng et al, 2020). APS has also been investigated for its enhancement of the immunity of COVID-19 patients (Adhikari et al, 2020;Meletis and Wilkes, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Honeysuckle is safe to be used as food and medicine because it has been used for thousand years of practicing TCM (Li RJ et al, 2020). Moreover, Huangqi is rich in the anti-viral immunomodulatory compound Astragalus polysaccharide (APS) (Shi et al, 2014;Xue et al, 2015;Wang et al, 2016;Zheng et al, 2020); thus, it may be effective against SARS-CoV-2 infections.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, 5 herbs that have the highest inhibitor effect are used including Herba agastaches, Flos chrysanthemi indici, Rhizoma anemarrhenae, Astragalus root, and Baikal skullcap root. The results suggested that formulation components have a synergistic effect to improve NDV resistance (Wang et al, 2016). These are some researches on Chinese herbal medicine in recent years for the control and treatment of the New Castle Disease Virus.…”
Section: Chinamentioning
confidence: 89%